Statement regarding three imprisoned British members of the International Brigade
1938-08 034-0141-007 "I have to thank you for your letter of May 13th regarding your son now in hospital here, a representative of the Consulate visited him recently and found his health greatly improved, I am keeping in close touch with his case." This letter, and the one from the Spanish Ambassador gave birth to the hope of the lad's liberation, but several letters addressed to the Hospital, Provincial De Valencia, since have been returned marked "not to be found." A few weeks ago news reached the lad's father of his lad's whereabouts from unexpected quarters. Will Hopkins, an ex Welsh miner and a member of the British Section of the International Brigade since April, 1937, escaped from a Spanish Prison in Puig near Sagunto on July 10th last. Hopkins resides at Aberaman, near Aberdare, and reports the plight of three members of the International Brigade in Puig. Corroborative evidence is available that W.J. Thomas has been in hospital the greater bulk of the time from the first week of September,1937, until the end of May, 1938. The three members of the International Brigade at "The Monastro, Puig, near Valencia, are:- W.J. Thomas of 5, Blackwells, Aberavon, Port Talbot, South Wales. Griffith Jones, of 13, Castle Row, Pengarnddu, Dowlais. James Kempton of 61, Whin Park, Cockenzie, East Lothian, Scotland. Through the information brought home from the prison in Puig by Will Hopkins contacts have been linked up by the relatives of the above-named. Will Hopkins definitely asserts that none of the three now lying in prison have been guilty of any crime. All of them have suffered serious illnesses, and although they have made every effort individually and collectively to get in touch with the Officers of the International Brigade their efforts have proved unavailing. Similarly the relatives of these three lads have hopelessly failed in their individual efforts. The father of Griffith Jones of Dowlais has been in correspondence with the British Consul in Valencia and the Spanish Aid Committee for many months, whilst Mrs. Kempton reports that she has had no news of her husband since November, 1937. 2. 292/946/34/144(iii)